Optimasi Matematika Untuk Penjadwalan Penanaman Tanaman Yang Efisien Dan Berkelanjutan - Ziliwu, Fince Mega Ceria; Prasetyo (CV. SINAR HOWUHOWU, 2025)
The scheduling of plant cultivation that is efficient and sustainable is a crucial aspect of agriculture to maximize agricultural output and maintain environmental sustainability. This study proposes the use of mathematical optimization methods to design a planting schedule that not only considers production factors but also long-term sustainability. The developed model integrates variables such as water requirements, sunlight, soil type, and seasons to ensure optimal plant cultivation. In this research, linear programming techniques and heuristic search algorithms are used to determine the planting schedule that provides the best results, considering resource limitations and ecological impacts. The results of this optimization model show an increase in agricultural production efficiency and contribute to environmental preservation.